Rancang Bangun Jig Rotor Sensor Untuk Proses Turning Pada Mesin CNC Lathe - Hendrayanto Wahyu Nugroho; Ali Imron; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
The manufacturing industry in Indonesia is growing rapidly. The development of the manufacturing industry makes consumer needs for manufactured products increase. One of the most commonly used automotive manufacturing products is Rotor Sensor. Rotor Sensor is one part in the ABS (Antilock Brake System) braking system in motorized vehicles. In the process of making Rotor Sensor products there are finishing processes, namely turning process on CNC lathe machines. This turning process requires a supporting device, a jig. Jig is one of the equipment holders of objects one to another to make the component doubling accurately. Therefore a jig is needed that can speed up the time of machining the Rotor Sensor product accurately according to the standard. Stages in designing a jig are understanding the shape, dimensions, and knowing the characteristics of the engine to be used for its production. To determine the design of the Rotor Sensor jig, three designs are made with different clamping systems. Calculation of cutting force and shear force is carried out to ensure that one stopper pin can hold the Rotor Sensor on the jig properly. Based on the results of the Rotor jig design the sensors for the turning process on the CNC lathe machine are produced jigs that can complete product machining within 34 seconds. The results of the turning process can be formed according to the standards used for Rotor Sensors with the average test producing acceptable products.